Community Foodborne of Salmonella Weltevreden Outbreak at Northern Governorate, Sultanate of Oman - Ali A. Al-Maqbali; Seif S. Al-Abri; V. Vidyanand; Idris Al-Abaidani; Amal S. Al-Balushi; Shyam Bawikar; Emadeldin El Amir; Saleh Al-Azri; Rajesh Kumar; Azza Al-Rashdi; Amina K. Al-Jardani (Springer, 2021)
Objectives: To investigate the course of a community gastroenteritis outbreak by Salmonella and implement interventional activities and roles to prevent occurring such an outbreak in the future. Methods: From August 27 to 2 September 2015, 101 individuals were reported among a local community. All affected individuals had a history of food consumption at a local restaurant. A rapid response team conducted active surveillance and interview with the affected individuals and workers of the restaurant. Food items and stools from food handlers and affected individuals were cultured and sent for genotyping. An environmental audit of the restaurant had been conducted. Results: The total majority of the affected individuals were male and more than 70% belonged to the young age group from 15 to 45 years. Out of the total, 97% had diarrhea, 70% fever, 56% abdominal cramps and 49% vomiting. All those affected were managed symptomatically except for 14 cases admitted for intravenous rehydration. Breakdown of food safety and basic personal hygiene were detected in the environment of the restaurant and among the workers. There are 39 out of 49 stool cultures of cases, six out of 18 food handlers, and five food samples were positive for Salmonella spp. The identical DNA fingerprinting pattern among S. Weltevreden strains originating from human cases and food was detected. Conclusion: This is the first reported community foodborne of S. Weltevreden outbreak in Oman. The importance of food safety and rigors environmental safety is emphasized. Basic personal hygiene and training of food handlers in restaurants are recommended with public health measurements.